Subjectivation by video—ethnographic explorations on practices of video analysis in high-performance youth football - Brümmer, C. (German Journal of Exercise and Sport Research, 2018)
This paper deals with video-based match and performance analysis in high-performance youth football. It draws on empirical material gathered during ethnographic research conducted with two teams organized within the framework of the youth academy of a German First Division football club. The material is analysed from a perspective inspired by sociological practice theories as well as the theoretical concept of subjectivation. The paper investigates the different contexts and practices of training in which videos occur and sheds light on their implications for the organization of play as well as for the development of players and coaches. Using long-term participatory observations and narratively designed qualitative interviews, it is revealed that videos serve different and heterogeneous purposes within different practices. Thus, this paper details not only the intended and obvious effects of video analysis, such as the optimization of play and training, but also its unintended and widely ignored side effects.